TSRS informatikų ir bibliotekininkų mokslinių mokyklų klausimu - Vilkina, Olga; Voverienė, Ona; Ringaitytė, Dalia (Knygotyra, 1991)
The base of the modern scientific schools is formed by essential scientific and economic problems. The authors analysed 1085 maintained thesis in the field of librarianship, bibliography and information science. These were the base for defining 11 directions of scientific research in information science, 11 — in librarianship, 7 — in bibliography. The scientific school in these fields is identified according to the social communication model of modern scientific school based on two types of communication relations: “a teacher — a student”, and collegiate. The results of research show that there is a scientific school of library theory and methodics established by O. Chubarjan which consists of 29 researches (three of them have doctor’s degree). There are no scientific schools in science information and bibliography.